Exploiting the impact of user-generated content on brand coolness and consumer brand engagement: A text-mining approach - Serras, Sara Alexandra Lopes (2020)
This dissertation aims to comprehend the impact of deploying user-generated content (UGC) campaigns on consumers’ perceptions of brand coolness and consumer brand engagement. The trending concept of coolness in the beauty industry is studied through electronic word of mouth to understand if brands encouraging their users to post about their brand experiences leads to consumers perceiving them as cool and engaging more positively through those publications. The methodology in use is a netnography, along with a sentiment analysis technique. The analysis consisted in observing the interactions, incited by a user-generated content campaign led by a prestigious beauty brand - Drunk Elephant, between the brand and its online brand community on the social network Instagram for one year to avoid seasonal phenomena. The comments were retrieved using a text-mining tool and analyzed through Natural Language Processing according to their sentiment polarity, and trending topics identified. The data retrieved from the year of 2019 amounted to 67 321 interactions. Results show consumers’ perceptions of coolness can be positively influenced by adopting UGC campaigns, which can also lead to positive consumer brand engagement. Not only do these campaigns generate brand awareness, but they stimulate brand community’s expansion and influence consumers’ perceptions towards the brand. Beauty brands seeking to grow their status of coolness and consumer interactions should consider implementing user-generated content campaigns, as keeping up with the trends in the market is not only regarded as cool but is necessary to remain relevant in the ever-changing marketplace beauty has proven itself to be.